1986
DOI: 10.1021/ja00275a085
|View full text |Cite
|
Sign up to set email alerts
|

Nickel-catalyzed intramolecular [4 + 4]-cycloadditions: a new method for the synthesis of polycycles containing eight-membered rings

Abstract: The nickel(0)-catalyzed oligomerization of 1,3-dienes holds a prominent place in the history and practice of organometallic chemistry as one of the first and most extensively studied transition-metal-catalyzed, C-C bond-forming reactions.1 In the case of buta-1,3-diene, this process selectively affords four-, six-, eight-, or twelve-membered rings, depending on catalyst ligands and reaction conditions.13 Notwithstanding its enormous synthetic potential, this chemistry has not been applied to complex molecule s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
44
0

Year Published

1992
1992
2013
2013

Publication Types

Select...
5
4

Relationship

4
5

Authors

Journals

citations
Cited by 173 publications
(44 citation statements)
references
References 1 publication
0
44
0
Order By: Relevance
“…[1,2] These studies have thus far produced the first examples of transition-metal-catalyzed [4þ4] cycloadditions of bisdienes, [3] [4þ2] cycloadditions of dienynes (and diene allenes), [4] [5þ2] cycloadditions of vinylcyclopropanes and p systems, [5] and [6þ2] cycloadditions of vinylcyclobutanones and p systems.[6] Recently, we started to investigate whether these and other two-component [mþn] cycloadditions could be converted into multicomponent [mþnþo…þx)] processes through trapping of the organometallic intermediates with additional components. [7] These investigations have thus far led to the first metal-catalyzed, three-component [5þ2þ1] cycloaddition reactions based on trapping of an intermediate in the [5þ2] cycloaddition reaction with CO.…”
mentioning
confidence: 99%
“…[1,2] These studies have thus far produced the first examples of transition-metal-catalyzed [4þ4] cycloadditions of bisdienes, [3] [4þ2] cycloadditions of dienynes (and diene allenes), [4] [5þ2] cycloadditions of vinylcyclopropanes and p systems, [5] and [6þ2] cycloadditions of vinylcyclobutanones and p systems.[6] Recently, we started to investigate whether these and other two-component [mþn] cycloadditions could be converted into multicomponent [mþnþo…þx)] processes through trapping of the organometallic intermediates with additional components. [7] These investigations have thus far led to the first metal-catalyzed, three-component [5þ2þ1] cycloaddition reactions based on trapping of an intermediate in the [5þ2] cycloaddition reaction with CO.…”
mentioning
confidence: 99%
“…In the course of our studies on the intramolecular [4+4] cycloaddition of bis-dienes, we observed, for example, a competing process, the nickel catalyzed [4+2] cycloaddition of a diene across an alkene ( 74 , Scheme 19). 58 This was not unexpected as Reppe and others had observed this competing pathway with simple butadienes. However, its utility in complex molecule synthesis was little advanced but potentially of great value, especially if it could be controlled in an intramolecular process similar to that which we observed with the [4+4] cycloaddition.…”
mentioning
confidence: 80%
“…57 In 1986, we reported the first nickel catalyzed intramolecular [4+4] cycloadditions as a strategy to overcome substitution problems and to control regio- and diastereoselectivity (Scheme 15). 58 Remarkably, the intramolecular process proved to be tolerant of diene substitution and proceeded with complete regioselectivity, high diastereoselectivity (97%) and high yield (93%), in part fueling our view that these reactions could provide “fundamentally new approaches to several structural classes including taxanes, ophiobolins, and fusicoccins”. The relationship of the cycloadduct stereochemistry and functionality to taxol is noteworthy and synthetically attractive as dihydroxylations of the double bonds would provide the B-ring oxidation pattern of this, then unsolved, target.…”
mentioning
confidence: 94%
“…For instance, nickel-catalyzed [4 + 4], [4 + 2], and [2 + 2 + 2] cycloadditions have received considerable attention. [11,12] Over the past decade, nickel-catalyzed reductive cyclizations and couplings have evolved into a broadly useful strategy for assembling synthetically versatile substructures and complex molecules. [13] Moreover, chiral nickel complexes are becoming potential practical catalysts in enantioselective transformations.…”
Section: Introductionmentioning
confidence: 99%